Synaptic Vesicle Exocytosis - Südhof, Thomas C. (Cold Spring Harbor Laboratory Press, 2011)
Presynaptic nerve terminals release neurotransmitters by synaptic vesicle exocytosis. Membrane fusion mediating synaptic exocytosis and other intracellular membrane traffic is affected by a universal machinery that includes SNARE (for “soluble NSF-attachment protein receptor”) and SM (for “Sec1/Munc18-like”) proteins. During fusion, vesicular and target SNARE proteins assemble into an α-helical trans-SNARE complex that forces the two membranes tightly together, and SM proteins likely wrap around assembling trans-SNARE complexes to catalyze membrane fusion. After fusion, SNARE complexes are dissociated by the ATPase NSF (for “N-ethylmaleimide sensitive factor”). Fusion-competent conformations of SNARE proteins are maintained by chaperone complexes composed of CSPα, Hsc70, and SGT, and by nonenzymatically acting synuclein chaperones; dysfunction of these chaperones results in neurodegeneration. The synaptic membrane-fusion machinery is controlled by synaptotagmin, and additionally regulated by a presynaptic protein matrix (the “active zone”) that includes Munc13 and RIM proteins as central components.